(untitled) (Clinics, 2015)
OBJECTIVE: This study was performed to determine the effect of N-acetyl-L-cysteine, a modified sulfur-containing amino acid that acts as a strong cellular antioxidant, on the response to environmental stressors and on aging in C. elegans. METHOD: The survival of worms under oxidative stress conditions induced by paraquat was evaluated with and without in vivo N-acetyl-L-cysteine treatment. The effect of N-acetyl-L-cysteine on the response to other environmental stressors, including heat stress and ultraviolet irradiation (UV), was also monitored. To investigate the effect on aging, we examined changes in lifespan, fertility, and expression of age-related biomarkers in C. elegans after N-acetyl-L-cysteine treatment. RESULTS: Dietary N-acetyl-L-cysteine supplementation significantly increased resistance to oxidative stress, heat stress, and UV irradiation in C. elegans. In addition, N-acetyl-L-cysteine supplementation significantly extended both the mean and maximum lifespan of C. elegans. The mean lifespan was extended by up to 30.5% with 5 mM N-acetyl-L-cysteine treatment, and the maximum lifespan was increased by 8 days. N-acetyl-L-cysteine supplementation also increased the total number of progeny produced and extended the gravid period of C. elegans. The green fluorescent protein reporter assay revealed that expression of the stress-responsive genes, sod-3 and hsp-16.2, increased significantly following N-acetyl-L-cysteine treatment. CONCLUSION: N-acetyl-L-cysteine supplementation confers a longevity phenotype in C. elegans, possibly through increased resistance to environmental stressors.